THE EFFECT OF PRODUCT INVOLVEMENT AND SOCIAL INFLUENCE ON ONLINE IMPULSE BUYING OF IBA STUDENTS - Bukidz, Rocky San Seaver; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The internet users in Indonesia is growing every year. Internet users use internet for various purposes one of them is for shopping. Students are one of the most active in using internet. Students especially in Manado city is known to actively use internet and have a consumptive lifestyle, thus it has a tendency for online impulse buying behavior. IBAâ€™s students are the part of the students in Manado city. There are some factors which affect online impulse buying some of them are product involvement and social influence. The main objective of this research is to determine the effect of product involvement and social influence on online impulse buying partially and simultaneously. This research used associative method with technique analysis is multiple regression analysis. The population in this research is all of the students of IBA program in Sam Ratulangi University who ever buy online products impulsively, whereas sample of respondents are 100 respondents. The result of this study shows that product involvement and social influence affect on online impulse buying simultaneously and partially. This study suggest to the marketers to continue develop online products that have relevance or relationship with the customer and also continued intensively to do promotions in social media. Â  Keywords: involvement, social influence, impulse buying